Front Cover: A Water‐Gated Organic Thin‐Film Transistor for Glyphosate Detection: A Comparative Study with Fluorescence Sensing (Chem. Eur. J. 64/2020). Issue 64 (14th October 2020) - Sasaki, Yui; Asano, Koichiro; Minamiki, Tsukuru; Zhang, Zhoujie; Takizawa, Shin‐ya; Kubota, Riku; Minami, Tsuyoshi
Abstract : A comparative study of a water‐gated organic thin‐film transistor (organic TFT) versus a fluorescence sensor chip and their sensitivity for herbicide glyphosate in water is reported in this work. A complex of a carboxylate‐functionalized polythiophene and a Cu 2+ ion was employed for the detection of glyphosate in both methods. In the cover artwork, the direction of the needle on the balance indicates that the water‐gated organic TFT exhibits higher sensitivity for glyphosate than the conventional fluorescence method. More information can be found in the Communication by T. Minami et al. on page 14525 .